Synergistic Effects of Zeolite and Organic Amendments on Soil Quality in Degraded Northern Guinea Savanna, Nigeria - Adamu, Auwal Bello; Lawal, Halima Mohammed; Abdulkareem, Jabir Haruna; Modu, Ayami Musa; Yahaya, Sharhabil Musa (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2026)
Background: Land degradation threatens crop productivity, particularly in savanna ecosystems where soils are inherently low in organic matter content and nutrient availability. Aim: This study evaluated the synergistic (integrated) effects of zeolite and organic amendments on selected soil chemical and physical properties of degraded Alfisols. Methods: A screen-house experiment was conducted in a randomized complete block design with ten treatments replicated three times. Four organic amendments: cow dung (CD), poultry litter (PL), biochar (BC), compost (CM), were applied at 5 t ha-1 and a control (CO), these treatments were used alone and in combination with zeolite applied at 5 g kg-1 of degraded soil.  In all treatments crops were augmented with the recommended NPK rate of sweet corn (Zea mays L. saccharata) as the test crop. Soil chemical and physical analyses were conducted using standard procedures after harvest. Results: Organic amendments significantly improved soil properties, with the overall performance following CM>PL>CD>BC>CO. Compost increased soil pH, organic carbon (OC), effective cation exchange capacity content (ECEC), saturated hydraulic conductivity (Ksat), and plant available water content (PAWC).  Total nitrogen (TN) content increased in the order PL>CM>CD>BC>CO. Zeolite conditioning further enhanced TN, ECEC, Ksat, and PAWC by 30.95%, 9.74%,13.09%, and 13.48% respectively while bulk density (BD) decreased by 3.40% compared to no zeolite-conditioned treatments. Conclusion: Overall, compost was the most effective organic amendment, and the integrated use of zeolite with organic amendments provide a practical, restorative strategy for improving nutrient retention and water availability for sustainable sweet corn production on degraded soils.